Health and Wellness Programming in Faith-Based Organizations: A Description of a Nationwide Sample. Issue 1 (January 2013) - Bopp, Melissa; Fallon, Elizabeth A.
Introduction . Most of the U.S. population is affiliated with faith-based organizations (FBOs) and regularly attends services. Health and wellness activities (HWA) delivered through FBOs have great potential for reach, but the number of FBOs offering health programs and the characteristics of these programs are currently unknown. The purpose of this study was to better understand rates, characteristics, and factors influencing faith-based HWA across the United States. Method . Faith leaders ( N = 844) completed an online survey assessing faith leader demographics and health, FBO demographics (e.g., denomination, size, location, diversity), and details of HWA within their FBO. Results . Respondents were primarily White (93%), male (72%), middle-aged (53.2 ± 12.1 years), and affiliated with Methodist (42.5%) or Lutheran (20.2%) denominations. Although most faith leaders report meeting physical activity recommendations (56.5%), most were overweight/obese (77.4%), did not meet fruit and vegetable recommendations (65.9%), and had been diagnosed with 1.25 ± 1.36 chronic diseases. Respondents reported offering 4.8 ± 3 HWA within their FBO over the past 12 months. Most common HWA included clubs/teams related to physical activity (54.8%), individual-level health counseling (54%), and providing health/wellness pamphlets. Leaders cited a lack of lay leadership (48.1%) and financial resources for staff time (47.8%) as the most common barriers to HWA. An increase in interest/awareness in health topics from FBO members was the most common facilitator for HWA (66.5%). Conclusion . Although faith-based HWA are prevalent nationally, types of HWA and the factors influencing HWA are dependent on FBO characteristics. Future faith-based interventions should consider existing capabilities and moderating factors for HWA.